Effects of different parameters on cellulase production by Trichoderma harzianum TF2 using solid‐state fermentation (SSF) - Jeffrey Lim Seng Heng; Halizah Hamzah (Universitas Gadjah Mada, 2022)
Solid‐state fermentation is one of the easiest and cheapest methods for producing microbial bioactive com‐ pounds. Trichoderma harzianum has long been recognised as one of the potential fungi for this purpose. Trichoderma sp. were isolated from banana rhizosphere using the soil dilution method and later screened for their ability to produce cellulases using filter paper activity (FPase) and the carboxylmethyl cellulase (CMCase) test. Trichoderma sp. were also subjected to one factor change at a time to determine the effects of different parameters on cellulase production. It was observed that T. harzianum TF2 showed the ability to produce higher cellulase activity when wheat bran was used as the substrate. The results showed that 38.5 U/g of cellulase was produced with the use of wheat bran coupled with an incubation temperature of 28 °C and moisture content of 60%. T. harzianum TF2 showed good potential for use as a culture for cellulase production in this study due to its higher cellulase production under solid‐state fermentation, with the possibility of its application to industry.